INFLUENCE OF INNOVATION OF FOREIGN TRADE ACTIVITIES OF TRANSPORT ENTERPRISES ON THE FORMATION OF THEIR COMPETITIVE ADVANTAGES - GRECHAN, Alla; BILIK, Volodymyr (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article identifies the specifics of the influence of innovativeness of foreign trade activities of transport enterprises on the formation of their competitive advantages. Specific features of the foreign trade activity of transport enterprises, which are areas of active implementation of innovative solutions, are analyzed. The use of technological innovations, innovative business models, innovations in supply chain management and customer service is proposed for transport enterprises. The main aspects and factors contributing to the effective implementation of innovative technologies in the field of international transportation are summarized. The following determinants of the development of foreign trade activities of transport enterprises are proposed: economic (global demand and supply, exchange rate fluctuations, investment climate), technological (innovation and technological progress, digitalization), political (regulatory policy, international agreements), social (level of personnel qualification, social guarantees ), Environmental (environmental standards and regulation, climate change). The key competitive advantages that transport enterprises can obtain thanks to innovations are identified, such as reducing operating costs, increasing operational efficiency, improving service quality, increasing environmental responsibility, flexibility and adaptability to market changes. The necessity of constant monitoring of the latest technological solutions and research of market trends to ensure the stable development of transport enterprises is substantiated. Prospects for further research are highlighted, in particular, the development of strategies for integrating transport systems with other sectors of the economy to create complex international logistics solutions.